Contribution of Hydrogen Sulfide to the Control of Coronary Blood Flow. (February 2014) - Casalini, Eli D.; Goodwill, Adam G.; Owen, Meredith K.; Moberly, Steven P.; Berwick, Zachary C.; Tune, Johnathan D.
Abstract Objective This study examined the mechanisms by which H2S modulates coronary microvascular resistance and myocardial perfusion at rest and in response to cardiac ischemia. Methods Experiments were conducted in isolated coronary arteries and in open‐chest anesthetized dogs. Results We found that the H2S substrate l‐cysteine (1–10 mM) did not alter coronary tone of isolated arteries in vitro or coronary blood flow in vivo. In contrast, intracoronary (ic) H2S (0.1–3 mM) increased coronary flow from 0.49 ± 0.08 to 2.65 ± 0.13 mL/min/g (p < 0.001). This increase in flow was unaffected by inhibition of Kv channels with 4‐aminopyridine (p = 0.127) but was attenuated (0.23 ± 0.02–1.13 ± 0.13 mL/min/g) by the KATP channel antagonist glibenclamide (p < 0.001). Inhibition of NO synthesis (l‐NAME) did not attenuate coronary responses to H2S. Immunohistochemistry revealed expression of CSE, an endogenous H2S enzyme, in myocardium. Inhibition of CSE with β‐cyano‐l‐alanine (10 μM) had no effect on baseline coronary flow or responses to a 15‐second coronary occlusion (p = 0.82). Conclusions These findings demonstrate that exogenous H2S induces potent, endothelial‐independent dilation of the coronary microcirculation predominantly through the activation of KATP channels, however, our data do not support a functional role for endogenous H2S in the regulation of coronary microvascular resistance.